(untitled) (Eurasian Journal of History, Geography and Economics, 2026)
Based on archival documents and state reports, this article highlights the reforms implemented in the field of physical culture and sports in the southern regions of Uzbekistan—Surxondaryo and Qashqadaryo regions—during the years of independence. The study analyzes the formation of the material and technical base of the sphere, the construction of modern sports facilities, and the activities of regional branches of the Fund for the Development of Children’s Sports of Uzbekistan. Furthermore, the indicators of public involvement in mass sports and the achievements of the oasis athletes in national and international competitions, particularly in kurash, judo, karate, chess, and football, are systematically investigated.